Les Extravagants chez Henri de Régnier: Des personnages en quête de certitudes - Silvia Rovera (Carnets)
In the late nineteenth century, the metamorphosis of society disoriented people who look for being different at any costs. Henri de Régnier, one of the writers most in vogue at the time, describes some of these people in his contemporary novels. This paper focused on the analysis of two novels: The midnight Marriage (1903) and The living Past (1905). In these writings, the author sketches the portrait of various types of extravagant people: dandies, collectors, lovers of the past and the occults.